Educational gender gaps and economic growth: A systematic review and meta-regression analysis - Anna Minasyan; Juliane Zenker; Stephan Klasen; Sebastian Vollmer (Georg-August-Universität Göttingen, Courant Research Centre - Poverty, Equity and Growth (CRC-PEG), 2018)
We conduct a systematic review and meta-analysis of the empirical literature on the impact of gender inequality in education on per capita economic growth, including cross-country, time series, and sub-national growth regressions. Studies using male and female education as separate covariates show a larger effect of female than male education on growth, except when an arguably problematic regression specification popularized by Barro and co-authors is used. We conduct a meta-regression analysis for studies that use the female-male ratio of education as explanatory variable. There we find evidence for a positive and statistically significant relationship between gender equality in education and growth based on 216 estimates from 17 such studies. We find that the average partial correlation coefficient between economic growth and the ratio of female over male education is 0.25, which is a moderate effect. The effect does not appear to be influenced by publication bias, it increases when one controls for initial education levels and social/institutional controls, while it falls with the use of fixed effects, the inclusion of economic controls, and the share of female authors.
Keywords: O47; I24; I25; 330; Gender gaps; Education; Growth; Systematic review; Meta-analysis